A Simple and Sensitive Electrochemical Sensor for 3-Nitrotyrosine Based on Electrochemically Anodic Pretreated Glassy Carbon Electrode in Anionic Surfactant Medium. Issue 15 (1st January 2019) - Zhai, Haiyun; Wang, Shiqiao; Zhou, Jianfeng; Pan, Jianbin; Tong, Yanli; Mei, Qinghua; Zhou, Qing
Abstract : A sensitive and facile electrochemical sensor based on glassy carbon electrode (GCE) receiving electrochemical anodic pretreatment for signal amplification was developed for the determination of 3-nitrotyrosine (3-NT) (an oxidative stress biomarker). Adding sodium hexadecyl sulfate (SDS) to 0.1 M HNO3 solution was conducive to adsorption onto the surface of modified electrode, which promoted electron exchange and enhanced electrochemical behaviors by significantly increasing the hydrophobicity of electrode surface. Scanning electron microscopy showed that the surface of modified GCE had a remarkably thin layer composed of dense nanoparticles owing to surface layer oxidation, growth of graphite oxide thin layer and microscopic mechanical destruction of electrode surface during cyclic voltammetry by anodization oxidation. Under optimal conditions, the current change of 3-NT in square wave stripping voltammetry (SWV) was linearly related to its concentration in the range of 0.05∼30.0 μM, with a detection limit (S/N = 3) of 17.0 nM, acceptable stability and reproducibility. Additionally, this sensor was successfully applied to detect 3-NT in human serum samples.